Wind Potential Assessment of Central Dry Zone of Indian State of Karnataka for Micro Power Generation - Himabindu N, K N Patil, Rajashekar P Mandi, Swapna Manasan, Santoshkumar Hampannavar, Venkatesh Murthy B S (International Journal of Advanced Science and Technology, 2020)
In this paper, wind potential assessment of a wind site located in central dry zone of Indian state of Karnataka is proposed using statistical distribution functions. Weibull and Rayleigh models were used for the statistical analysis of real wind speed data for complete one year. Wind rose diagram was plotted to study the wind direction and velocity. The results obtained were promising in terms of wind power densities and Raleigh model best suits for Chitradurga wind site.